Campaign Disaster Response – What Makes It Different. (5th August 2023) - Zeitz, Kathryn; Kay, Rachael; Naughton, David; Bennett, Scott; Bolton, Shane
Abstract: Objective: The coronavirus disease 2019 (COVID-19) pandemic has seen health systems adapt and change in response to local and international experiences. This study describes the experiences and learnings by the Central Adelaide Local Health Network (CALHN) in managing a campaign style, novel public health disaster response. Methods: Disaster preparedness has focused on acute impact, mass casualty incidents. In early 2020, CALHNs largest hospital the Royal Adelaide Hospital (RAH) was appointed as the state primary COVID-19 adult receiving hospital. Between the period of February 1, 2020, when the first COVID-19 positive patient was admitted, through to December 31, 2020, the RAH had admitted 146 inpatients with COVID-19, 118 admitted to our hospital in the home service, 18 patients admitted to Intensive Care, and 4 patients died while inpatients. During this time CALHN has sustained an active (physical and virtual) Network Incident Command Centre (NICC) supported by a Network Incident Management Team (NIMT). Results: This study describes our key lessons learnt in relation to the management of a campaign style disaster response including the importance of disaster preparedness, fatigue management, and communication. Also described, were the challenges of operating in a command model and the role of exercising and education and an overview of our operating rhythm, how we built capability, and lessons management. Conclusions: Undertaking a longer duration disaster response, relating to the COVID-19 pandemic has shown that, although traditional disaster principles still are important, there are many nuances that need to be considered to retain a proportionate response. Our key lessons have revolved around the key tenants of disaster management, communication, capability, and governance.